Policy proposal on development of research topics of graduate students at the Faculty of Education, Naresuan University - Thirasak Uppamaiathichai; Passkornr Roueangrong (Journal of Green Learning, 2021)
This research paper is a policy summary for developing af research topics of graduate students. The selection of 12 proposals were sampled by purposive sampling. The framework in policy proposal on development consisted of 1) Department of Education, 2) Department of Education Administration and Development, 3) Department of Educational Technology and Communications, and 4) Department of Physical Education and Exercise Science. The results showed that the plicy proposal is an appropriate and feasibilily.